Un viajero nacionalista por los Andes: Comentario a propósito de una nueva edición de ‘Paisajes peruanos’, de José de la Riva-Agüero y Osma - Gómez Acuña, Luis (2023)
Paisajes peruanos (‘Peruvian landscapes’) is one of the best historical-literary works created by the historian José de la Riva-Agüero y Osma. It has always been called a travel memoir, which of course was quite unique. A Limenian young man, with a doctorate in Letters from the University of San Marcos, descendant of the ancient Peruvian colonial nobility, undertook a journey through the Andes in 1912, roughly following the colonial path between Cusco and Huancayo. His travel notes became later an erudite polyphonic travel story, with clear modernist prose. Moreover, Paisajes peruanos is also a clear vision of what the young liberal Riva-Agüero thought the Peruvian nation was and should be.